Analisis Pengaruh Kemampuan Sumber Daya Manusia pada Kinerja Perbendaharaan di BPPKAD Kabupaten Intan Jaya - Yusuf, Ivan; Jaya, Amir; Buku, Atus (Green Publisher Indonesia, 2025)
The Regional Revenue, Finance, and Asset Management Agency (BPPKAD) plays a vital role in regional financial management. This study aims to analyze the influence of human resource (HR) capabilities on treasury performance at BPPKAD Intan Jaya Regency. This research is qualitative in nature, using both primary and secondary data obtained through observation, interviews, and documentation. The informants in this study are four BPPKAD employees who have an understanding of HR capabilities and treasury performance. The data analysis method used is descriptive qualitative, consisting of data collection, data reduction, data presentation, and drawing conclusions. The results show that: 1) The level of competence and skills of HR at BPPKAD Intan Jaya is crucial in supporting treasury performance, where the majority of employees have a good understanding of accounting and financial management, contributing to the accuracy of financial reports. 2) Internal factors influencing HR performance include leadership, management support, and a supportive organizational culture. External factors include government policies, geographical location, and public demand. 3) HR capabilities affect the effectiveness and efficiency of treasury performance, where trained and competent employees can make accurate decisions, prepare accurate financial reports, and manage budgets well. This indicates that good analytical skills can enhance financial management in BPPKAD.